Female Migrant Workers under Patriarchal Society: Case Study in Taiwan - Gouw, Safina Al Shifa Chandra; Sudirman, Arfin; Hakiki, Falhan (Buana Gender: Jurnal Studi Gender dan Anak, 2025)
Through the lens of normative feminism, this article examines the many difficulties experienced by female migrant workers within Taiwan's patriarchal framework. Taiwan's economy has mostly benefited from the labor of migrant workers, most of whom are women. Because of the country's pervasive patriarchal system, these workers frequently face complex gender-based problems. This study explores the overlapping layers of marginalization, exploitation, and discrimination faced by female migrant workers via the lens of normative feminist theory, drawing attention to the many difficulties that these women face as a result of Taiwan's patriarchal norms interacting with the job market, social structures, and cultural prejudices. Utilizing non-participatory observation and internet-based literature research, this article finds that there is a lack of research on gender-based factors that cause these challenges. Though there has been international support from labor protection-focused organizations, there are still limitations and loopholes in the existing legal protections available in Taiwan and sending countries of these workers, causing cases of risks faced by female migrant workers go undocumented at a large number. This study pushes forth the urgency for more robust instruments and government bodies that bind and regulate the treatments and protections towards these female migrant workers.